Citotaxonomia dos triatomíneos: a citogenética como ferramenta no estudo do complexo Triatoma brasiliensis e do subcomplexo Brasiliensis - Alevi, Kaio Cesar Chaboli [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Cytogenetic analyzes have shown to be important tools to study the taxonomy of the triatomines. Thus, the use of cytogenetic techniques may clarify the problems existing in the current classification of species that form the Brasiliensis subcomplex. The species in the subcomplex were grouped only by morphological data and geographical distribuition and differs from the species in the Triatoma brasiliensis complex, on the basis of on different approaches that indicate the monophyly. The present paper describes cytogenetically T. lenti, T. sherlocki, T. melanocephala and T. vitticeps, in order to evaluate the position of these vectors in the Brasiliensis subcomplex and analyze a possible relationship of T. lenti, T. melanocephala and T. vitticeps with the T. brasiliensis complex. Classical cytogenetic analysis (Lacto-acetic orcein, silver nitrate staining and C banding) and molecular (in situ hybridization - FISH) were performed in adult males. T. lenti and T. sherlocki showed several chromosomal characteristics in common, such as the number of chromosomes (2n = 20A + XY), disposition of constitutive heterochromatin in the autosomes (one or both ends of the autosomes) and the staining of nucleolar organizer regions (NORs) (a pair of autosomes). These insects were able to be differentiated by markings observed in spermatids, which were proposed as a diagnostic tool cytotaxonomic. T. melanocephala and T. vitticeps shared the chromosome number (2n = 20A + X1X2X3Y) and the same characteristics during spermatogenesis. However, these vectors were able to be differentiated by the disposition of heterochromatic blocks, by the arrangement of NORs and the examination of spermiogenesis. Thus, these characteristics corroborate the position of T. lenti and T. sherlocki on Brasiliensis subcomplex and and we propose the exclusion of T. melanocephala, T. vitticeps and T. tibiamaculata because they present fragmentation of the sex chromosome X and are ...

As análises citogenéticas têm se mostrado como importantes ferramentas para o estudo da taxonomia dos triatomíneos. Dessa forma, a utilização de técnicas citogenéticas poderá esclarecer a problemática existente na classificação atual das espécies que compõem o subcomplexo Brasiliensis. Essas espécies foram agrupadas apenas por dados morfológicos e pela distribuição geográfica e diferem das espécies agrupadas no complexo Triatoma brasiliensis, com base em diferentes abordagens que levaram à indicação da monofilia. O presente trabalho descreve aspectos citogeneticos de T. lenti, T. sherlocki, T. melanocephala e T. vitticeps, com o intuito de avaliar a posição desses vetores no subcomplexo Brasiliensis e analisar uma possível relação de T. lenti, T. melanocephala e T. vitticeps com o complexo T. brasiliensis. Análises citogenéticas clássicas (Orceína Lacto-Acética, Impregnação por íons prata e Bandamento C) e moleculares (Hibridização in situ – FISH) foram realizadas em machos adultos. T. lenti e T. sherlocki, que apresentaram muitas características cromossômicas em comum, como o número de cromossomos (2n = 20A + XY), disposição da heterocromatina constitutiva nos autossomos (uma ou ambas as extremidades dos cromossomos) e na disposição das Regiões Organizadoras Nucleolares (RONs) (um par de autossomos). Esses insetos foram diferenciados por meio de marcações observadas nas espermátides, o que foi proposto como ferramenta citotaxonômica diagnóstica. T. melanocephala e T. vitticeps apresentaram o mesmo número de cromossomos (2n = 20A + X1X2X3Y) e as mesmas características durante a espermatogênese. No entanto, esses vetores puderam ser diferenciados pela disposição dos blocos heterocromáticos, pela disposição das RONs e pela análise da espermiogênese. Assim, com base nessas características, corroboramos a posição de T. lenti e T. sherlocki no subcomplexo Brasiliensis e propomos a ...
Keywords: Biologia; Citogenética; Triatoma - Classificação; Biologia - Classificação; Espermatogenese em animais; Barbeiro (Inseto); Cytogenetics